High Power 190 GHz Frequency Doubler Based On GaAs Schottky Diode - Nan Wu; Zhi Jin; Jingtao Zhou; Haomiao Wei; Zhicheng Liu; Jianming Lin (IEEE Journal of the Electron Devices Society, 2024)
The research on high power 190 GHz doubler based on the GaAs Schottky diodes is proposed in this paper. The frequency doubler comprises a improved diode configuration that increases the number of anodes by changing the diode arrangement to improve power handling capacity. Electromagnetic and thermal simulation is utilized to demonstrate that the doubler can carry more power. The input power is gradually pumping from 200 mW to 500 mW with an applied DC bias of −15 V. And the peak efficiency of the doubler is measured to be 17%, while the maximum output power is 85 mW at 190 GHz.